Tingkat Bahaya Longsor Di DAS Klagison Kota Sorong Menggunakan Sistem Informasi Geografis - Anif Farida; Febrianti Rosalina (EcoNews, 2022)
On September 16, 2020, landslides occurred in Sorong City covering Sorong District (Klademak, North Remu), North Sorong (Malaingkedi), and Sorong Manoi (Malabutor). The three affected sub-districts are in the Klagison watershed area where the upstream has a fairly steep slope. The purpose of this study was to determine the level of landslide hazard in the Klagison watershed based on the parameters of rainfall, slope, soil type, rock type, and land cover using Geographic Information Systems. The method used is an overlay of five parameters that affect landslides by weighting and scoring to produce a landslide hazard level map. The results showed that the Klagison watershed was divided into three classes of landslide hazard levels: low (1.180,66 Ha), medium (442,45 Ha), and high (244,52 Ha).